ANALYSIS OF THE READINESS OF LOCAL GOVERNMENTS IN IMPLEMENTING GOVERNMENT REGULATION NUMBER 12 OF 2019 CONCERNING REGIONAL FINANCIAL MANAGEMENT - Arif Gunabar Fatahillah; Yesi Mutia Basri; Desmiyawati Desmiyawati (Berkala Akuntansi dan Keuangan Indonesia, 2021)
This study aims to analyze the readiness of the Kampar Regency Government in implementing PP No. 12 of 2019. The population in this study is all SKPD in the Kampar district, amounting to 48 SKPD. The sampling technique using saturated sampling method. A total of 112 respondents participated in the research consisting of Budget User Proxy, Technical Implementation Officials of Activities, Head of Finance Subdivision, and Financial Staff Staff. The data collection technique is carried out by using questionnaires which is sent directly to the respondent. The results of the analysis using multiple regressions show Human Resource Competence, Utilization and Use of Technology and Information, Leadership Style affects Readiness in Implementation of Government Regulation No.12 of 2019. The results of this study have contributed to the government in preparing for the implementation of regulatory changes.